Sistem Deteksi Posisi Gajah Berbasis Frekuensi Radio - Agus Urip Ari Wibowo; Rizki Dian Rahayani; Arif Gunawan; Wahyuni Khabzli (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
This paper is motivated by the human-elephant conflict that often occurs due to the narrowing of the elephant habitat caused by industrial and residential interests. In addition, the habitat breadth and the lack of elephant keepers also becomes a consideration. In this paper, we propose an elephant detector using radio frequency. The detector using KYL-200L as transmitter is mounted on the elephant necklace and the sensor nodes as transceivers are installed at some point in the outer boundaries of the elephant habitat. When an elephant is moving within the sensor node radius, the node will send information to the server to be displayed on surveillance computer, and an alert will be sent via SMS to the elephant keeper. The result shows that the maximum communication distance range obtained is 190 m, depending on the propagation and geographical location of the nodes. The average delay of SMS sending is 4.74 seconds depending on providers’traffic service. The differences on the elephant position detection caused by SMS delay are insignificant compared to the radius of the nodes and the elephant habitat.